2015
DOI: 10.1016/j.neuroimage.2014.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive neural networks for guilty feelings in young adults

Abstract: Feelings of guilt are associated with widespread self and social cognitions, e.g., empathy, moral reasoning, and punishment. Neural correlates directly related to the degree of feelings of guilt have not been detected, probably due to the small numbers of subjects, whereas there are growing numbers of neuroimaging studies of feelings of guilt. We hypothesized that the neural networks for guilty feelings are widespread and include the insula, inferior parietal lobule (IPL), amygdala, subgenual cingulate cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…Remarkably, in the present study M1-SO and DLPFC montages produced significant peaks of electric current in the PFC, a region intrinsically related to cognitive and emotional functions (Gusnard et al, 2001 ; Phelps et al, 2004 ; Tabibnia et al, 2014 ; Haas et al, 2015 ; Kong et al, 2015 ; Nakagawa et al, 2015 ) and thus important for the modulation of the emotional dimension of pain (Lorenz et al, 2002 ; Porro et al, 2002 ; Apkarian et al, 2004 ; Kuchinad et al, 2007 ; DaSilva et al, 2008 ; Boggio et al, 2009b ; Metz et al, 2009 ; Jin et al, 2013 ; Baliki et al, 2014 ; Bogdanov et al, 2015 ). Based on the results of the current study, it is possible to speculate that not only DLPFC tDCS but also M1-SO produces its clinical effects through direct PFC modulation.…”
Section: Discussionsupporting
confidence: 48%
“…Remarkably, in the present study M1-SO and DLPFC montages produced significant peaks of electric current in the PFC, a region intrinsically related to cognitive and emotional functions (Gusnard et al, 2001 ; Phelps et al, 2004 ; Tabibnia et al, 2014 ; Haas et al, 2015 ; Kong et al, 2015 ; Nakagawa et al, 2015 ) and thus important for the modulation of the emotional dimension of pain (Lorenz et al, 2002 ; Porro et al, 2002 ; Apkarian et al, 2004 ; Kuchinad et al, 2007 ; DaSilva et al, 2008 ; Boggio et al, 2009b ; Metz et al, 2009 ; Jin et al, 2013 ; Baliki et al, 2014 ; Bogdanov et al, 2015 ). Based on the results of the current study, it is possible to speculate that not only DLPFC tDCS but also M1-SO produces its clinical effects through direct PFC modulation.…”
Section: Discussionsupporting
confidence: 48%
“…The capacity for interoception is correlated with the ability to understand the emotions of others [ 36 ], and indeed, the posterior insular cortex has been shown to be involved in emotional functioning. For example, previous studies have shown that greater gray matter volume in the posterior insula is associated with guilty feelings, which are related to empathy [ 37 ], and that there is a reduction in gray matter volume in patients with cognitive alexithymia [ 38 ]. Because greater gray matter volume in the posterior insula is associated with the recognition of self and of other’s emotional status, it is reasonable to expect that praising a child frequently would facilitate the development of empathy.…”
Section: Discussionmentioning
confidence: 99%
“…IPS guilt mainly refers to situations in which a friend is hurt, whereas RBS guilt is more public and sometimes involves specific others (parents). For more details, please refer to our previous study 7 .…”
Section: Methodsmentioning
confidence: 99%
“…shame and embarrassment) 6 . A previous brain grey matter (GM) anatomical study conducted by our group directly demonstrated that scores related to feelings of guilt in both interpersonal and rule-breaking situations were uniquely and negatively related to regional GM density (rGMD) in the right posterior insula (PI) 7 . To the best of our knowledge, no studies have used diffusion tensor imaging (DTI) to assess the correlation of guilt feelings and white-matter (WM) structure, including WM volume (WMV).…”
Section: Introductionmentioning
confidence: 92%